Exploration of the ordering for a sequential airport ground movement algorithm - Ravizza, Stefan; Atkin, Jason A.D. (School of Computer Science, 2011)
Guiding aircraft around the airport's surface while ensuring conflict-free routings is an important problem at airports. Sequential routing and scheduling algorithms can be advantageous for providing fast online solutions for decision support systems to help controllers. However, the effectiveness of such algorithms can depend upon the sequence of consideration of the aircraft, which is often chosen to be first-come-first-served. This research analyses the effects of different heuristics to find better sequences. Results are presented, utilising real data from Zurich Airport. These show that sophisticated heuristics can substantially improve the solution with comparatively little additional computational time. Furthermore, one approach aims to modify relatively few existing routes as it progresses, in order to minimise the workload of the controllers in communicating changes in an online environment.